Pengembangan Pelayanan Perpustakaan Sekolah Menggunakan Visual Basic 2010 - Nofri Hendri (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
Library services is in need of computer role. Lots of book data that must be processed in order to avoid overlapping of data errors or the book. If the library does not have a library of application it will really make the librarian should be a lot of wasted time to collect data library books alone. School library service development using Visual Basic 2010 needs to be done to be more effective. This study aimed to produce school library services using Visual Basic 2010 in accordance with eligibility criteria and a media library. This type of research is the development of research. Products developed through five phases: 1) planning, 2) Early Product Development, 3) Product Validation, 4) Trial, and 5) Produk.Alat of collecting data was a questionnaire. Data on quantitative descriptive analysis to determine product quality. The research model is a model of procedural development with research subjects 4 respondents, consisting of two people validator media experts and two experts validator library UNP ie, 2 lecturers, and two librarians FIP UNP. Samples were librarians SMP Negeri 1 district. Guguak kab. 50 City.